Pparg may Promote Chemosensitivity of Hypopharyngeal Squamous Cell Carcinoma - Meng Lian; Jiaming Chen; Xixi Shen; Lizhen Hou; Jugao Fang (PPAR Research)
The upregulation of peroxisome proliferator-activated receptor gamma (PPARG) has been shown to increase the chemosensitivity of several human cancers. This study is aimed at studying if PPARG sensitizes hypopharyngeal squamous cell carcinoma (HSCC) in chemotherapeutic treatments and at dissecting possible mechanisms of observed effects. We integrated large-scale literature data and HSCC gene expression data to identify regulatory pathways that link PPARG and chemosensitivity in HSCC. Expression levels of molecules within the PPARG regulatory pathways were compared in 21 patients that underwent chemotherapy for primary HSCC, including 12 chemotherapy-sensitive patients (CSP) and 9 chemotherapy-nonsensitive patients (CNSP). In the CPS group, expression levels of PPARG were higher than that in the CNSP group (log‐fold‐change=0.50). Structured text mining identified two chemosensitivity-related regulatory pathways driven by PPARG. In the CSP group, expression levels for 7 chemosensitivity-promoting genes were increased, while for 13 chemosensitivity suppressing the gene expression levels were decreased. Our results support the chemosensitivity-promoting role of PPARG in HSCC tumor cells, most likely by affecting both cell proliferation and cell motility pathways.